Empowering early childhood educators to foster spatial and numeracy reasoning through play-based learning - Winarti, Destina Wahyu; Widjaja, Wanty; Razi, Fakhrur; Huzaimah, Sitti; Prianggi, Assila; Setyawan, Iwan Aries (Journal on Mathematics Education, 2025)
Despite the growing awareness of the importance of spatial reasoning in schooling years, there is a notable gap in research literature to promote spatial reasoning in early childhood education in Indonesia. This research aims to address this gap by building the capacity of Indonesian early childhood educators in designing play-based activities to support children’s spatial thinking and reasoning. Twenty early childhood education (ECE) educators coming from different area in Java, Indonesia participated in the study. The study employed design-based research methodology to examine the way in which research team and ECE educators work collaboratively to bring about innovative learning processes and changes in ECE’s practices. A key design principle of the study features play-based activities to promote children’s spatial reasoning skills in the early years were analyzed.  This study finds that the professional learning program provides support for ECE educators in three areas, such as foster an understanding of key numeracy concept including one-to one correspondence and cardinality and how it is being implemented, offer insights about spatial ability and its constructs, and exposure to spatially rich play-based activities that could be adopted for ECE centers.